Scalable Carbon Black Enhanced Nanofiber Network Films for High‐Efficiency Solar Steam Generation. Issue 24 (12th November 2021) - Zhang, Rong; Zhou, Yuewei; Xiang, Bo; Zeng, Xujia; Luo, Yanlong; Meng, Xiangkang; Tang, Shaochun
Abstract: Developing cost‐effective interfacial solar steam generation devices based on advanced structured materials for water desalination is highly desired. Herein, a high‐efficiency solar steam generation based on a novel solar energy receiver of carbon black (CB)‐based composite nanofiber networks with designed integrated 2D water path is reported. The receiver having a two‐layer structure is prepared by a one‐step electrospinning a suspension of CB particles in cellulose acetate (CA) onto a porous PET substrate. The upper hydrophilic CA/CB nanofiber layer works for light absorption and water evaporation and the bottom hydrophilic PET layer is vertically inserted into the water to act as 2D water path in charge of water pumping for improved efficiency of water supply and minimized heat loss. The solar evaporator demonstrates an ultrahigh evaporation rate of 1.48 kg m –2 h –1 and solar energy conversion efficiency of 98.6% under 1 kW m –2 (1‐sun) illumination. Especially, the conversion efficiency is much superior over the values of the most previous ones, while the developed technique offers great potential for low‐cost and large‐scale production. Abstract : A highly efficient and cost‐effective solar steam generator based on a novel solar energy receiver of carbon black‐based composite nanofiber networks with designed integrated 2D water path is developed. This system is promising for large‐scale application due to the easily scalable electrospinning process.